Analisis Standar Penilaian pada Satuan Pendidikan Dasar dan Menengah di Indonesia - Umi Baroroh; Sukiman Sukiman (Lembaga Sosial Rumah Indonesia, 2023)
Assessment is an important and inseparable part of the educational process. The importance of this assessment component is proven by the existence of Minister of Education and Culture Regulation Number 23 of 2016 concerning Assessment Standards for Primary and Secondary Education levels which was later updated with Minister of Education and Culture Regulation No. 21 of 2022 as a consequence of changes in the curriculum in Indonesia. This research aims to analyze the Education Assessment Standards in Minister of Education and Culture Regulation Number 23 of 2016 and Minister of Education and Culture Regulation Number 21 of 2022. This research uses a qualitative approach with the type of research being a literature study (library research). Data analysis was carried out in three stages, namely data condensation, data display, and drawing conclusions. This research found that in Minister of Education and Culture Regulation Number 23 of 2026, Educational Assessment Standards include criteria regarding scope, objectives, benefits, principles, mechanisms, procedures and assessment instruments. Meanwhile, in Permendikbudristek Number 21 of 2022, it was found that the Education Assessment Standards include minimum criteria regarding assessment mechanisms.